If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + (-9) = (-3) + 7 5 + -9 = (-3) + 7 Combine like terms: 5 + -9 = -4 -4 = (-3) + 7 -4 = -3 + 7 Combine like terms: -3 + 7 = 4 -4 = 4 Solving -4 = 4 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 4+88-n*n=9n | | P^2+4P+5=0 | | 3x-5(x-4)=6+3x+11 | | 3x+10=3x+20 | | 111=-3(1-8m)5m | | 7/y=20 | | 3+5n=2n*n | | 3(r-6)+2=4(r+2)21 | | 1/2d-5=8 | | (8*2)*(5-n)=n*n-2 | | m/-2=4 | | 4+2n-4=2+4n-2 | | 5/a=4/a-8 | | 3+4n=4+3n | | 8/7*-4 | | 10(x-1)+(x+4)+4x=24 | | 4r-36=2r+14 | | 738.410/9.05 | | 0.5(x-3)-(1.5-x)=5x | | 9+2=10 | | 11x+4=x+195 | | X-5+3=20 | | 11x+4=4x+195 | | 2(5-2y*7)= | | 5w-7+5(3w-4)= | | -234=6(-6x-3) | | 3x^2+17x-4=0 | | x-3/4=21 | | (2x^2D^2+4xD+7)y=logx^2 | | -6(6b+4)=156 | | 4a^4+36a^2+72= | | -(11x-5)-(2x-6)+6=-5(x-1)-(13x+6)+3 |